Veterinary professional identity: Conceptual analysis and location in a practice theory framework - Scholz, Emma; Trede, Franziska (Frontiers in Veterinary Science, 2023)
Professional, social, and cultural issues and phenomena of veterinary practice are now established areas of commentary and interest in research, education, professional publications and even in the mainstream media. Despite the availability of theoretically informed literature in diverse relevant domains and disciplines including professional practice, workplace learning, and medical sociology and anthropology, commentary and research on veterinary practice issues and phenomena remains dominated by clinician-educators and clinician-policymakers. Reflecting the clinical disciplinary traditions, there is a resulting over-representation of individualistic, positivist perspectives and under-theorised research studies. In this paper we provide an interdisciplinary theoretical framework for veterinary practice and veterinary professional identity grounded in a practice theory perspective. We begin by arguing for the need for such a framework by scoping veterinary practice in its contemporary social context. We go on to provide a sociocultural framing of veterinary practice, underlining the mutual constitution of individuals and the social world through participation in practices and taking into consideration important concepts including knowledge, institutions, ethics, and embodiment. We assert the importance of professional identity as a core phenomenon of veterinary practice, constituted by making meaning of professional practice experiences, especially through narrative and dialogue. This practice theory framework for veterinary practice and veterinary professional identity development provides rich opportunities for understanding, researching, and enacting diverse activities and phenomena, especially learning, development and change within and beyond formal educational settings.